"MANAGING CYBER SECURITY RISKS IN ISLAMIC FINTECH: A SHARIAH PERSPECTIVE" (Contemporary Journal of Social Science Review, 2025)
Financial inclusion in the global Muslim population has been transformed by the rapid growth of Islamic Fintech (i-Fintech) to offer alternative solutions, which are Shariah-compliant, to traditional banking with the help of Artificial Intelligence (AI) and Block chain. Nonetheless, this electronic transformation has come with a lot of cyber security threats that are not only threatening the financial resources, but also the Islamic virtue of Trust (Thiqah). This paper resolves a gap in the literature in that it investigates the nexus between digital security and Islamic jurisprudence. The research is based on a qualitative exploratory research design consisting of systematic content analysis and 18 in-depth interviews with Shariah scholars, cyber security professionals, and fintech executives to evaluate how technical security measures are applied in accordance with the Objectives of Shariah (Maqasid al-Shariah). The main results show that there is a high level of agreement between the experts (88.6) that there is a religious requirement to ensure a strong cyber security level. This paper presents the idea of Data Amanah (Divine Trust) that data negligence is violated as a religious obligation. This study leads to the development of the proposal of a Shariah-Compliant Cyber security Framework (SCCF). This framework unites international technical standards (e.g., Zero-Trust Architecture and Quantum-Resistant Encryption) with such ethical pillars as Privacy by Design and Technical Shariah Audits. In the end the research comes to the conclusion that cyber security is the new jurisprudence of protection of wealth, which is necessary to ensure the material and spiritual interests of the stakeholders in the digital economy of the Islamic world.